Truncation and constitutive activation of the androgen receptor by diverse genomic rearrangements in prostate cancer - Henzler, Christine; Li, Yingming; Yang, Rendong; McBride, Terri; Ho, Yeung; Sprenger, Cynthia; Liu, Gang; Coleman, Ilsa; Lakely, Bryce; Li, Rui; Ma, Shihong; Landman, Sean R.; et al. (Nature communications, 2016)
Molecularly targeted therapies for advanced prostate cancer include castration modalities that suppress ligand-dependent transcriptional activity of the androgen receptor (AR). However, persistent AR signalling undermines therapeutic efficacy and promotes progression to lethal castration-resistant prostate cancer (CRPC), even when patients are treated with potent second-generation AR-targeted therapies abiraterone and enzalutamide. Here we define diverse AR genomic structural rearrangements ( AR -GSRs) as a class of molecular alterations occurring in one third of CRPC-stage tumours. AR -GSRs occur in the context of copy-neutral and amplified AR and display heterogeneity in breakpoint location, rearrangement class and sub-clonal enrichment in tumours within and between patients. Despite this heterogeneity, one common outcome in tumours with high sub-clonal enrichment of AR -GSRs is outlier expression of diverse AR variant species lacking the ligand-binding domain and possessing ligand-independent transcriptional activity. Collectively, these findings reveal AR -GSRs as important drivers of persistent AR signalling in CRPC. Castration-resistant prostate cancer frequently presents with persistent androgen receptor signalling. Here, the authors find that the androgen receptor is subject to genetic rearrangements, resulting in variants with ligand-independent activity.